Clinical pathological features and prognosis of diabetic nephropathy patients with stage 4 chronic kidney disease - YU Tian-yu; JIANG Shi-min; YANG Yue; FANG Jin-ying; GAO Hong-mei; ZOU Gu-ming; LI Wen-ge (Linchuang shenzangbing zazhi)
Objective To investigate the relationship of clinical manifestations and pathological features with prognosis of diabetic nephropathy（DN） patients with stage 4 chronic kidney disease（CKD）.Methods The study subjects were those patients,who were diagnosed as DN by renal biopsy pathology with renal function in stage 4 CKD in Department of Nephrology of Chino-Japan Friendship Hospital from January 2005 to August 2019.The follow-up deadline was either the primary endpoint or until November 30,2019.The primary endpoints of observation were initiation of maintenance kidney replacement therapy,death or estimated glomerular filtration rate（eGFR） less than 15 mL·min-1·（1.73 m2）-1.The secondary endpoints were cardiovascular and cerebrovascular events.Based on the pathological classification of renal biopsy,the clinical and pathological parameters of the patients were respectively analyzed and survival analysis was performed.Results A total of 24 patients were included in the study,3 cases of type Ⅱa,with 3 cases of type IIb,15 cases of type III and 3 cases of type IV.The total median follow-up time was 20.7（range 5.9～72.4） months.The total median survival time was 17.3 months.7 patients with stage 4 CKD were still maintained,with the median follow-up time of 14.6（range 5.9～46.8） months;17 patients developed the primary endpoint event,with the median follow-up time of 14.2（range 6.1～72.4） months.The renal cumulative survival rates in 6 months,12 months and 18 months were 82.6%,59.3% and 41.6%,respectively.The comparison between the two groups with and without the primary endpoint events showed that systolic blood pressure and cardiovascular events were statistically different（P<0.05）.Conclusions The median survival time of progression to composite kidney endpoint events in DN patients with stage 4 CKD is 17.3 months.Control level of blood pressure and cardiovascular events might be the major relevant factors in progression of renal function.